The Concept of Exemplary Stories in Religious Maturity at Kindergarten - Suci Istriana; Rahman, Imas Kania; Indra, Hasbi (Program Studi Magister Pendidikan Islam,Sekolah Pascasarjana Universitas Ibn Khaldun Bogor, 2024)
Children aged 5-6 years or equivalent to Kindergarten level B should be presented with real stories that can be used as examples. Unfortunately, most parents at home and teachers at school still read their children more fictitious stories, commonly called fairy tales. Therefore, the intake of exemplary stories containing uswatun hasanah is needed to help children achieve religious maturity following the stages of their age development. This research aims to find the concept of exemplary stories in religious maturity in kindergarten. The researcher used a qualitative approach by using a literature study. The findings of this study are exemplary story materials in religious maturity that have been conceptualized specifically for kindergarten. The findings of this exemplary story concept material can be used by kindergarten teachers to increase the religious maturity of students in terms of faith, worship, and morals. Abstrak Anak-anak usia 5-6 tahun atau setara dengan Taman Kanak-kanak tingkat B seharusnya disuguhkan dengan kisah-kisah nyata yang dapat dijadikan teladan. Sayangnya, kebanyakan orang tua di rumah dan guru di sekolah masih lebih banyak membacakan anak-anaknya cerita-cerita khayalan yang bersifat fiktif atau biasa disebut dongeng. Oleh karena itu, asupan kisah-kisah teladan yang mengandung uswatun hasanah sangat dibutuhkan untuk membantu anak mencapai kematangan beragama sesuai dengan tahapan perkembangan usianya. Tujuan penelitian ini adalah menemukan konsep kisah teladan dalam kematangan beragama pada taman kanak-kanak. Peneliti menggunakan pendekatan kualitatif dengan menggunakan studi literatur. Temuan dari penelitian ini adalah materi kisah teladan dalam kematangan beragama yang telah dikonsep khusus untuk taman kanak-kanak. Temuan materi konsep kisah teladan ini dapat digunakan oleh para guru taman kanak-kanak dalam meningkatkan kematangan beragama anak didik dalam sisi akidah, ibadah, dan akhlak.